Driving Success: The role of inclusive leadership in fuelling employee performance through the mediating role of job motivation - niazi, aiman; Atika Fazil (UW Journal of Management Sciences, 2025)
Purpose: The study aims to contribute to the literature on inclusive leadership by establishing and testing the relationship between inclusive leadership and employee outcomes i.e., task performance and innovative work behaviour. The study further seeks to establish the mediating role of job motivation in the said association. Design and Methodology: The study used a quantitative research methodology to test the hypothesis and derive conclusions. Survey-based data was collected from 164 managerial and non-managerial level employees from IT sector organizations in the twin cities of Punjab province, Pakistan. The collected data was analysed through the statistical software SPSS to generate findings that support the established hypothesis. Findings: The results confirmed several key relationships. Inclusive leadership not only directly improves innovative work behaviour but also plays a crucial role in enhancing job motivation, ensuring employees feel valued and motivated. This motivated state of employees is linked to enhanced innovative work behaviour, reinforcing the notion that motivated employees contribute significantly to organizational success. However, the study reveals non-significant direct and indirect relationship of inclusive leadership with employee task performance. Implications: The research will provide IT sector organizations with detailed comprehension into the dynamics of leadership style and its subsequent impact on employee motivation and workplace behaviours.